Russian ﬁnancial market development strategic initiatives under sanctions and in the aftertime - K. L. Astapov (Мир новой экономики)
New challenges and restrictions, imposed by a number of countries, affected the Russian ﬁnancial system and real sector of economy, so implementation of responsive strategic decisions to support ﬁnancial and real sectors of the economy is necessary. The study’s goal is to develop proposals for ﬁnancial market strategy in new conditions, to support investment opportunities for Russian investors and investors from friendly and neutral countries, to control capital ﬂow in the medium term. The research result is the justiﬁcation of the new model of the Russian ﬁnancial system, which is based not only on liberal economic paradigm but also on realities of economic pressure on our country. In the current crisis, it is advisable to have two models of the ﬁnancial market: the ﬁrst is based on recognized international principles, which applied to large public Russian companies; the second is focused on companies under sanctions and regional business. Strengthening regulation of cross-border capital movement, including introduction of strict restrictions on capital withdrawal, as well as limits on operations on foreign exchange market, are seen not only as temporary anti-crisis instruments of state regulation, but as the basis for strategy construction for the ﬁnancial market development. Support of the state development institutions, commercial banks and large corporations of the limited interaction model with developed countries will reduce systemic risks not just in critical periods, but also in the future. Therefore, this can attract resources to real investment projects and stimulate the growth of the capitalization of Russian companies.